The Association and Mediators Between Sleep Problems in Autistic Children and Parenting Stress - Tang M; Li M; Huang M; Liu L; Zhu L; Chen Y (Psychology Research and Behavior Management)
Meiling Tang,1,2,* Min Li,1,* Meijiao Huang,1 Lu Liu,3 Linping Zhu,4 Yongjun Chen1 1The Affiliated NanhuaHospital, Department of Neurology, Hengyang Medical College, University of South China, Hengyang, Hunan, 421002, People’s Republic of China; 2The Affiliated NanhuaHospital, Hengyang Medical College, Department of Pediatrics, University of South China, Hengyang, Hunan, 421002, People’s Republic of China; 3The Affiliated NanhuaHospital, Hengyang Medical College, Department of General Medicine, University of South China, Hengyang, Hunan, 421002, People’s Republic of China; 4The Affiliated NanhuaHospital, Hengyang Medical College, Department of Gastrointestinal Surgery, University of South China, Hengyang, Hunan, 421002, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yongjun Chen, The Affiliated NanhuaHospital, Department of Neurology, Hengyang Medical College, University of South China, Hengyang, Hunan, 421002, People’s Republic of China, Email Cd20240823@163.com Min Li, The Affiliated NanhuaHospital, Department of Neurology, Hengyang Medical College, University of South China, Hengyang, Hunan, 421002, People’s Republic of China, Email lim-usc@qq.comPurpose: To investigate the association among sleep problems in autistic children, emotional symptom in autistic children and parenting stress.Methods: This study recruited a total of 292 children with autism in two special education schools in Hunan province, China. The average age of the autistic children in this study was 6.5 ± 2.8 years. Sleep problems in autistic and parenting stress were measured by Youth Self-Rating Insomnia Scale (YSIS), Sleep Disturbance Scale for Children (SDSC), and The Parenting Stress Index-Short Form (PSI-SF-15). The main analysis included latent profile analysis, multivariate logistic regression analysis, and mediation analysis.Results: The prevalence for sleep disturbance and insomnia symptoms in autistic children were 38.7% and 13.0%, respectively. Parenting stress was divided into three groups: low-risk group (81 participants, 28%), middle-risk group (134 participants, 46%), and high-risk group (77 participants, 26%). Sleep problems (insomnia and sleep disturbance) and emotional symptoms (anxiety and depression) in children with autism were risk factors for parental stress. Depressive symptom in autistic children was significant in mediating the relationship between insomnia symptoms and parenting stress.Conclusion: There is a significant effect of sleep problems in autistic children, as these sleep issues can substantially increase parental stress, with depressive symptoms in autistic children serving as a positive mediator.Keywords: sleep problems, sleep disturbance, parenting stress, emotional symptom, autistic children